2011
DOI: 10.1002/ca.21265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thoracic pedicle morphometry in a Chinese population using 3D reformatted CT

Abstract: The aim of this study was to investigate the detailed three-dimensional morphology of the pedicles from T1 to T12 in 120 Chinese patients using a light-speed Vct CT (General Electric). After reformatting the original images, the following parameters were studied: outer pedicle width (OPW), outer pedicle height (OPH), pedicle chord length (PCL), pedicle cortical thickness (PCT) of the isthmus, and transverse pedicle angle (TPA). The mean outer pedicle width, outer pedicle height, and pedicle chord length were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The parameters measured in the current study for each subject included pedicle width and pedicle length. The measurement method is described below [29,36]. The guideline was defined as the straight-line perpendicular to the axis of the vertebra that passed through the anterior tip of the vertebral canal.…”
Section: Measurement Of Morphologic Features Of the Pediclementioning
confidence: 99%
“…The parameters measured in the current study for each subject included pedicle width and pedicle length. The measurement method is described below [29,36]. The guideline was defined as the straight-line perpendicular to the axis of the vertebra that passed through the anterior tip of the vertebral canal.…”
Section: Measurement Of Morphologic Features Of the Pediclementioning
confidence: 99%
“…On the other hand, both their CSAs ( y = −5.665 + 0.591 × age ± 1.251, y = −11.281 + 0.853 × age ± 1.653) and volumes ( y = −9.279 + 0.849 × age ± 2.302, y = −16.117 + 1.155 × age ± 1.832) followed linearly. Ossification progression within the neural processes is relevant in the diagnosis of neural tube defects [ 5 , 20 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies such as Carmouche et al, 21 cited in this review, have clearly demonstrated the correlation between increased insertional torque and increased pullout resistance in osteoporotic bone. This is likely due to the advantage it provides in achieving greater bony purchase of cortical bone, which can be highly variable between patients due to age, 48 as well as demonstrated differences between men and women. 34 In recent biomechanical studies, it has been demonstrated that the density of the bone in contact with the screw threads is strongly correlated with POS.…”
Section: Discussionmentioning
confidence: 99%